Project Implementation Management Strengthening Pancasila Student Profile and Rahmatan Lil 'Alamin Student Profile at MAN 1 Musi Banyuasin - Erdiansyah; Zainal Berlian; Maryamah (Didaktika: Jurnal Kependidikan, 2024)
The curriculum in the Industrial 4.0 era demands developments that can produce graduates with the latest literacy, including data literacy, technical literacy, and human literacy oriented towards noble morals and independence. This study observes the implementation of the Independent Curriculum, especially the Strengthening the Profile of Pancasila and Rahmatan Lil 'Alamin Students (P5P2RA) Project, at MAN 1 Musi Banyuasin. The results highlight organized management approaches, success factors, and obstacles faced, including budget and facility challenges. Data collection techniques involve in-depth interviews, participatory observation, and documentation. Research instruments are in the form of interview guidelines, question lists, and observation sheets. The collected data will be analyzed using data reduction techniques, data presentation, data verification, and conclusions. The results showed that the management of the Pancasila and Rahmatan Lil 'Alamin student profile projects faced complex challenges, including team coordination, busy participants, technical obstacles, and evaluation. To address this, a holistic approach is needed with a focus on open communication, schedule flexibility, careful technical planning, and continuous evaluation. Through effective coordination and joint efforts, schools can ensure project success and deliver a sustainable positive impact. This initiative not only creates an inclusive learning environment but also strengthens participants' skills in achieving a learner profile that reflects the values of Pancasila and the spirit of Rahmatan Lil 'Alamin.